CROWN ROOTLESS1 binds DNA with a relaxed specificity and activates OsROP and OsbHLH044 genes involved in crown root formation in rice. (9th July 2022) - Gonin, Mathieu; Jeong, Kwanho; Coudert, Yoan; Lavarenne, Jeremy; Hoang, Giang Thi; Bes, Martine; To, Huong Thi Mai; Thiaw, Marie‐Rose Ndella; Do, Toan Van; Moukouanga, Daniel; Guyomarc'h, Soazig; Bellande, Kevin; et al.
SUMMARY: In cereals, the root system is mainly composed of post‐embryonic shoot‐borne roots, named crown roots. The CROWN ROOTLESS1 (CRL1) transcription factor, belonging to the ASYMMETRIC LEAVES2‐LIKE/LATERAL ORGAN BOUNDARIES DOMAIN (ASL/LBD) family, is a key regulator of crown root initiation in rice ( Oryza sativa ). Here, we show that CRL1 can bind, both in vitro and in vivo, not only the LBD‐box, a DNA sequence recognized by several ASL/LBD transcription factors, but also another not previously identified DNA motif that was named CRL1‐box . Using rice protoplast transient transactivation assays and a set of previously identified CRL1‐regulated genes, we confirm that CRL1 transactivates these genes if they possess at least a CRL1‐box or an LBD‐box in their promoters. In planta, ChIP‐qPCR experiments targeting two of these genes that include both a CRL1‐ and an LBD‐box in their promoter show that CRL1 binds preferentially to the LBD‐box in these promoter contexts . CRISPR/Cas9‐targeted mutation of these two CRL1‐regulated genes, which encode a plant Rho GTPase ( OsROP ) and a basic helix–loop–helix transcription factor ( OsbHLH044 ), show that both promote crown root development. Finally, we show that OsbHLH044 represses a regulatory module, uncovering how CRL1 regulates specific processes during crown root formation. Significance Statement: CRL1, a lateral organ boundary domain transcription factor controlling crown root initiation in rice ( Oryza sativa ), binds two distinct DNA sequences and activates the expression of several genes whose promoters contain these motifs. Knockout of two identified CRL1‐regulated genes, OsROP and OsbHLH044, showed that these two genes contribute to crown root formation downstream of CRL1 and that OsbHLH044 represses a gene regulatory module during this process.